Narasi Pelepasan Emosi dalam Kajian Genre Healing Fiction sebagai Media Katarsis - Ummah, Nadia Wirda; Puspitasari, Diana; Suryadi, Yudi; Widodo, Heri (KIRYOKU, 2025)
Healing fiction is a genre in literary works that has a theme about healing, both spiritually and emotionally. The characters who appear in the healing fiction genre are described as finding inner peace and trauma recovery through the process of self-introspection, courage to face problems, relationships with others and relationships with nature. The healing fiction genre with its narrative that depicts characters who finally find inner peace, allows readers to experience emotional catharsis. This research will look at how the narrative elements of the healing fiction genre can be a vehicle for readers to experience the cathartic process. This research will use the narrative text analysis approach of Japanese novels with the healing fiction genre. This research will also use a thematic analysis approach to find out readers' responses. Reading works in the healing fiction genre can be a cathartic medium because it presents a feeling of relief like what happens in the process of accidental pleasure.